1070. Epidemiological and Clinical Features of Panton–Valenton Leukocidin-Positive Staphylococcus aureus Bacteremia: A Case–Control Study. (26th November 2018) - Kausar, Humera; Smith, Stephen; Qu, Ming Da; Lazar, Peter G; Kroll-Desrosiers, Aimee; Barton, Bruce; Ward, Doyle V; Ellison III, Richard T
Abstract: Background: The presence of the binary Panton-Valentine Leukocidin (PVL) toxin in Staphylococcus aureus has been associated with both severe pneumonia and skin and soft-tissue infections. However, there is only limited data on how this virulence factor impacts S. aureus bacteremia and whether it might affect the clinical course or complications of bacteremic infections. Methods: Between September 2016 and March 2018, a convenience sample of S. aureus isolates from clinical cultures obtained in inpatient units and the Emergency Departments of UMass Memorial Medical Center underwent comprehensive genomic sequencing. Four hundred sixty-nine (29%) of 1, 681 S. aureus sequenced isolates were identified as containing the LukF and LukSPV genes that encode for PVL. Case patients with one or more positive blood cultures for LukF/LukSPV + strains were randomly matched with control patients having positive blood cultures for LukF/LukSPV − strains for a retrospective chart review. Results: The 55 case and 56 control patients were comparable in age and gender; case patients were more likely to have a history of injection drug use, while controls more likely to undergo hemodialysis or have had indwelling IV catheters. Case patients more commonly had chest pain and more prolonged fever; but had the same incidence of sepsis and septic shock. Isolates from 42 (76%) of case patients were methicillin resistant as compared with 16 (29%) from control patients. Elevations in serum creatinine and alkaline phosphatase were more common in control patients. Case patients had a higher incidence of pneumonia, with no differences seen in the incidence of endocarditis, osteomyelitis, or septic arthritis. The percentage of patients who were clinically cured or expired were comparable. Conclusion: These results are consistent with prior observations associating the PVL toxin with community-acquired MRSA strains as well as severe staphylococcal pneumonia. However, it does not appear to otherwise influence the natural history of bacteremic S. aureus disease other than in prolonging the duration of fever. Disclosures: All authors: No reported disclosures.